TEACHING CRITICAL LISTENING TO YOUNG LEARNERS IN INDONESIAN EFL CONTEXT - Fetty Poerwita Sary (Indonesian EFL Journal, 2015)
The teaching of English in Indonesia includes four skills—listening, speaking, reading, and writing, and two language components—vocabulary and grammar. Listening is one of the four language skills that have an important role in teaching of English in our country. In the context of early childhood education—including the teaching of English in elementary school—there has been a persistent misconception about how children learn—including learning a foreign language. To ensure success in learning a foreign language, children should have a great deal of exposure to, engagement in, and support for the language they are learning. Therefore, the aims of the study are to know the response of the young learners in learning listening skill through storytelling and whether they can apply the critical listening into the other language skills—speaking, reading, and writing. The subjects in this study are students of level 3 in one of English course in Bandung Indonesia. Their ages are around 9 -12 years old. The data are gathered from activities in the classroom, observation, and interviews. This reseach provides steps of critical listening activities. The results shows 1) the activities are sucessfully help the students to sharpen their listening skill and 2) most of the students can apply the listening skills to the other skills. In the end of this study, the pedagogical implications were provided.Keywords: critical listening, young learners, Indonesian EFL context.